Analysis of bulk negative capacitance field effect transistor - Rahman, Towfiqur; Khan, Antara Fairooz; Nawal, Nowshin (BRAC University, 2017)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2017.